REVOLUTIONIZING AYURVEDA: THE CONVERGENCE OF RESEARCH, INNOVATION, AND ENTREPRENEURSHIP (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
For centuries, Ayurveda has been deeply rooted in ancient wisdom, passed down through classical texts such as the Charaka Samhita, Sushruta Samhita, and Ashtanga Hridaya. However, the 21st century is witnessing a paradigm shift—Ayurveda is being redefined, restructured, and revalidated through scientific research, technological advancements, and entrepreneurial breakthroughs.